Keseimbangan Kehidupan-kerja Karyawan: Apakah Terus Bertahan pada Pekerjaannya atau Keluar? - Tsabitah, Anisa Hasna; Widiasih, Puti Archianti (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2024)
This study aims to analyze the relationship between work-life balance and turnover intention, with affective commitment as a moderating variable. An imbalance in work-life balance can increase employees' desire to leave their jobs, whereas affective commitment has the potential to weaken this effect. The research employs a quantitative approach with a causal-comparative design. Data were collected through an online questionnaire involving 250 employees from the industrial and service sectors in Indonesia, selected using the purposive sampling technique. Data analysis was conducted using the Moderated Regression Analysis (MRA) technique to examine the relationships among variables. The results indicate that work-life balance has a negative effect on turnover intention, meaning that the better an individuals work-life balance, the lower their likelihood of leaving their job. Furthermore, affective commitment was found to be a moderating variable that weakens the relationship between work-life balance and turnover intention. The findings highlight the importance of organizations in fostering work-life balance while strengthening employees' affective commitment through organizational strategies that promote well-being and emotional engagement. Future research is recommended to expand the sector coverage and use longitudinal methods to better understand the long-term effects of work-life balance on turnover intention.